AICA Congress in Poland in 1960: â€œInternational Character of Contemporary Artâ€ - Genova, Irina (Sledva : NBU Journal of Humanities and Arts, 2020)
The art historian prof. Irina Genova traces the history of AICA (Association internationale des critiques dâ€™art) and focuses on its congress in Poland (Warsaw and Krakow) in 1960. The carefully chosen topic of the congress, â€œInternational Character of Contemporary Artâ€, meant to provide a meeting point for Western European and Eastern European artists and to open the post-Stalinist Eastern art scene to the contemporary tendencies of the abstract painting. The situation was different in the different countries. The research draws a parallel between the quite open Polish scene and the more conservative and closed Bulgarian one and the reception the congress had in those two contexts.